THE INFLUENCE OF WORK-LIFE BALANCE ON PSYCHOLOGICAL WELL-BEING IN SINGLE-PARENT FAMILIES IN JELBUK, JEMBER - Muhtadin, Sabilul; Subhan, Suhuf; Saifulloh, Kholid (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
Work-life balance (WLB) is an important factor in determining psychological well-being, especially for single-parent families who must face challenges in dividing their roles as breadwinners and child caregivers. This study aims to analyze the influence of work-life balance on the psychological well-being of single parents in Jelbuk, Jember. Using a correlational quantitative method, this study involved a sample of single parents who have lived in this condition for at least two years, selected using the Stratified Random Sampling technique. Data were collected through interviews, observations, documentation, and questionnaires, then analyzed using the Pearson Product Moment correlation test with the help of SPSS software. The results of this study are expected to provide insight into the relationship between work-life balance and single parents' psychological well-being. The findings will also provide recommendations for community-based interventions that can help single parents achieve better balance. From an Islamic perspective, the concept of balance between the world and the hereafter is an important basis for understanding work-life balance, as reflected in Qur'anic verses and hadith. Thus, this research not only provides academic contributions but also practical insights that can be applied in social life.